Occupational Stress of Farm Scientists Working in Agricultural Universities - Chandan Kumar Panda and Sarthak Chowdhury, (Indian Journal of Extension Education, 2018)
Right from the day of entering into service till the day of retirement, a farm scientist is invariably exposed tovarious stressful situations for one reason or others. In the field of work and organizational psychology, too,the concept of stress has obtained its own position under job stress. Stress is the mental and physical condition.The stress of the farm scientists was measured through the Occupational Stress Indicator (OSI) scale ofCooper et al. (1987) and Job Satisfaction was measured with the Quin and Shepard (1974) Scale. Thisresearch work was conducted in Bidhan Chandra Krishi Viswavidyalaya and Uttar Banga KrishiViswavidyalaya. The complete enumeration method was followed and sample size was ninety six. Majorcontributing factors associated with the occupational stress of the farm scientist were organizationalcommunication, task performance, skills utilization and psychological “feel” in organization and out of thesefour factors task performance was the best single predictor of job satisfaction in relation to OSI. Twenty twovariables were clustered in six factors.